1985
DOI: 10.1080/00071668508416824
|View full text |Cite
|
Sign up to set email alerts
|

Influence of various nesting materials on nest site selection of the domestic hen

Abstract: Nesting behaviour of LSL hens from a deep litter house and from a battery system was compared. Every hen was tested in one of two trial chambers containing a wire mesh floor and a nest unit with 5 nesting materials: wire mesh, perforated plastic, synthetic grass, wheat straw and oat husk. Wheat straw and oat husk were preferred as nesting materials to perforated plastic, synthetic grass and wire mesh. The results from these trials were confirmed in a deep litter house. After the nesting material, oat husk, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 5 publications
2
16
0
Order By: Relevance
“…However, in the present study illumination of the litter mat did not reduce the proportion of eggs laid there, a result in agreement with Appleby et al (1984), suggesting that factors other than light intensity are of considerable importance for selection of nest site in layers. It has been suggested that when hens are group housed, social factors contribute to hens laying outside the nest box (Cronin et al,, 2009), Also, earlier studies indicate that loose substrate such as straw or wood shavings enhances the attractiveness of nests (Huber et al, 1985;Appleby and Smith, 1991). Although most of the daily portion of saw dust delivered on the litter mat was finished in a rather short time, saw dust particles were more or less incorporated in the turf and for some individuals this may be a stronger nest attribute than nest itself.…”
Section: Use Of Nests and Egg Qualitymentioning
confidence: 97%
“…However, in the present study illumination of the litter mat did not reduce the proportion of eggs laid there, a result in agreement with Appleby et al (1984), suggesting that factors other than light intensity are of considerable importance for selection of nest site in layers. It has been suggested that when hens are group housed, social factors contribute to hens laying outside the nest box (Cronin et al,, 2009), Also, earlier studies indicate that loose substrate such as straw or wood shavings enhances the attractiveness of nests (Huber et al, 1985;Appleby and Smith, 1991). Although most of the daily portion of saw dust delivered on the litter mat was finished in a rather short time, saw dust particles were more or less incorporated in the turf and for some individuals this may be a stronger nest attribute than nest itself.…”
Section: Use Of Nests and Egg Qualitymentioning
confidence: 97%
“…Hens prefer to lay in enclosed or secluded nest sites (Duncan et al, 1978;Appleby and Smith, 1991), and work harder for access to enclosed nest sites than for open nest sites (Cooper and Appleby, 1994 a). Hens also prefer nest sites with mouldable or peckable nest-building substrates (Wood-Gush and Murphy, 1970;Huber et al, 1985;Duncan and Kite, 1989;Reed and Nicol, 1992). Hens may, therefore, floor lay, not because they are less motivated to seek out and use a nest site, but because man made nest boxes are poorly designed and unattractive.…”
Section: Introductionmentioning
confidence: 96%
“…79 The importance of the nest box is based on evidence of preference tests, evidence of frustration in the absence of a nest and the strong motivation of hens to use a nest. [80][81][82][83] Hens prefer litter to a wire floor, [84][85][86] although it is not clear if litter is an important resource for hens. 78 Evidence of frustration includes restlessness, stereotyped escape behaviour and prolonged searching behaviour prior to oviposition and directing nest building towards an apparently inappropriate substrate such as wire.…”
Section: Nest Boxesmentioning
confidence: 99%